Government intervention, internal control, and technology innovation of SMEs in China - Ye, Sun; Yi, Sun; Fangjing, Shao; Yuzhu, Qi (Frontiers in Psychology, 2022)
Under the innovation-driven development strategy, the improvement of the core competitiveness of enterprises demonstrates increasing dependence on the ability of technological innovation. Data of A-share listed companies in Shanghai and Shenzhen stock markets from 2008 to 2018 were selected as research samples in this paper for the analysis of the influencing factors and mechanism of enterprise technological innovation from the dual perspectives of external economic environment and internal management system based on the use of fixed effect model. The results show that government intervention significantly hinders investment of enterprises in resources for technological innovation, and less government intervention can improve innovation investment of enterprises. The intervention of internal control fails to bring institutional advantages; rather it aggravates the negative effect of government intervention on enterprise technological innovation. The research not only enriches the existing academic research results on government intervention, internal control quality and enterprise technological innovation, but also provides experience for accelerating the process of Marketization in China, enterprise governance and improving the level of enterprise technological innovation.